Excuse me while I disappear : tales of midlife mayhem - Notaro, Laurie (Little A, 2022)
Laurie Notaro has proved everyone wrong: she didn't end up in rehab, prison, or cremated at a tender age. She just went gray. At past fifty, every hair's root is a symbol of knowledge (she knows how to use a landline), experience (she rode in a car with no seat belts), and superpowers (a gray-haired lady can get away with anything). Though navigating midlife is initially upsetting, the cracking noises coming from her new old body, receiving regular junk mail from mortuaries, Laurie accepts it. And then some. With unintentional abandon, she shoplifts a bag of russet potatoes. Heckles a rude driver from her beat-up Prius. And engages in epic trolling on Nextdoor.com. That, says Laurie, is the brilliance of growing older. With each passing day, you lose an equivalent amount of fear.